Impact of legitimacy, innovation and economic uncertainty on the purchase of electric vehicles in the EU - Delso-Vicente, Alberto-Tomás; Diaz-Marcos, Luis; Aguado-Tevar, Óscar; Almonacid-Durán, Margarita (Revista Venezolana de Gerencia, 2025)
The aim of this study is to analyse the interaction between legitimacy, innovation, uncertainty and purchase intention of electric vehicles (EVs) in Germany, Greece, Spain, France, Croatia, Ireland and Italy during the period 2016–2023. The partial least squares structural equation modelling (PLS-SEM) technique is used. Thee main results indicate that legitimacy has a significant and positive impact on purchase intention, while innovation affects legitimacy but not directly on purchase intention. Uncertainty moderates these relationships in complex ways. The findings suggest that strengthening the perception of legitimacy is crucial to increasing EV purchase intention. Furthermore, strategies that promote innovation and manage uncertainty can improve market acceptance in these countries.